Thermodynamics of Peptide-MHC Class II Interactions: Not all Complexes are Created Equal - Ferrante, Andrea (Frontiers in Immunology, 2013)
The adaptive immune response begins when CD4+ T cells recognize antigenic peptides bound to class II molecules of the Major Histocompatibility Complex (MHCII). The interaction between peptides and MHCII has been historically interpreted as a rigid docking event. However, this model has been challenged by the evidence that conformational flexibility plays an important role in peptide-MHCII complex formation. Thermodynamic analysis of the binding reaction suggests a model of complexation in which the physical-chemical nature of the peptide determines the variability in flexibility of the substates in the peptide-MHC conformational ensemble. This review discusses our understanding of the correlation between thermodynamics of peptide binding and structural features of the resulting complex as well as their impact on HLA-DM activity and on our ability to predict MHCII-restricted epitopes.